Digital microfluidics on paper - Matos, Daniel Correia de (2015)
This thesis is one of the first reports of digital microfluidics on paper and the first in which the chip’s circuit was screen printed unto the paper. The use of the screen printing technique, being a low cost and fast method for electrodes deposition, makes the all chip processing much more aligned with the low cost choice of paper as a substrate. Functioning chips were developed that were capable of working at as low as 50 V, performing all the digital microfluidics operations: movement, dispensing, merging and splitting of the droplets. Silver ink electrodes were screen printed unto paper substrates, covered by Parylene-C (through vapor deposition) as dielectric and Teflon AF 1600 (through spin coating) as hydrophobic layer. The morphology of different paper substrates, silver inks (with different annealing conditions) and Parylene deposition conditions were studied by optical microscopy, AFM, SEM and 3D profilometry. Resolution tests for the printing process and electrical characterization of the silver electrodes were also made. As a showcase of the applications potential of these chips as a biosensing device, a colorimetric peroxidase detection test was successfully done on chip, using 200 nL to 350 nL droplets dispensed from 1 μL drops.